MAKNA DENOTATIF DAN KONOTATIF EMPAT KUTIPAN MILIK SAGE PADA PERMAINAN VALORANT: KAJIAN SEMANTIK - Parji, Rahmelia Prastamawati; Prihandini, Asih (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2023)
This research aims to analyze the words in the Sage’s quotes one of the characters in the Valorant game, which has denotative and connotative meaning. The meaning of denotative word is word that has an actual meaning as it is written in the dictionary. Whereas the meaning of connotative word is word that has a meaning according to suggestion, or what is associated with a word that goes beyond its formal definition. Connotations are personal associations produced by words. Denotation is an objective relationship between the linguistic form and to which it refers. An example in one of the quotes is